p53 in trichostatin A induced C6 glioma cell death - Hsu, Ya-Fen; Sheu, Joen-Rong; Hsiao, George; Lin, Chien-Huang; Chang, Tsai-Hsing; Chiu, Pei-Ting; Wang, Chun-Yu; Hsu, Ming-Jen (Biochimica et biophysica acta, 2011)
BACKGROUND: Histone deacetylase (HDAC) inhibitors were demonstrated to induce cell cycle arrest, promote cell differentiation or apoptosis, and inhibit metastasis. HDAC inhibitors have thus emerged as a new class of anti-tumor agents for various types of tumors. However, the mechanisms by which HDAC inhibition-induced cell death remain to be fully defined. METHODS: In the present study, we explored the apoptotic actions of trichostatin A (TSA), a HDAC inhibitor, in C6 glioma cells. RESULTS: TSA activated p38 mitogen-activated protein kinase (p38MAPK), leading to p53 phosphorylation and activation. P53, a proapoptotic transcription factor, in turn transactivated the expression of a proapoptotic protein, Bax. In addition, survivin, a member of inhibitor of apoptotic protein, was significantly decreased in TSA-treated C6 cells. P53 recruited to the endogenous survivin promoter region was increased and accompanied by decreasing recruitment of SP1 in response to TSA. TSA was also shown to induce IKK dephosphorylation and to suppress NF-κB reporter activity. CONCLUSIONS: TSA may cause C6 cell apoptosis through activating p38MAPK–p53 cascade resulting in Bax expression and survivin suppression. Negative regulation of IKK–NF-κB signaling may also lead to p53 activation and contribute to TSA apoptotic actions. GENERAL SIGNIFICANCE: TSA-induced p53 activation may occur through p53 modification by phosphorylation or by acetylation via IKK inactivation. The present study delineates, in part, the signaling pathways involved in TSA-induced glioma cell death.